On moduli of smoothness and Fourier multipliers in L_p, 0 < p < 1 - Kolomoitsev, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We obtain the theorem on the relationship between a modulus of smoothness and the best approximation in L p , 0 < p < 1, and theorems on the extension of functions with the preservation of the modulus of smoothness in L p , 0 < p < 1. In addition, we present a complete description of multipliers of periodic functions in the spaces L p , 0 < p < 1.